Optimal Activation of Porous Carbon for High Performance CO2 Capture. Issue 6 (17th May 2016) - Lee, Ji Hoon; Kwac, Kijeong; Lee, Hyeon Jeong; Lim, Soo Yeon; Jung, Dae Soo; Jung, Yousung; Choi, Jang Wook
Abstract: Various porous materials have shown a great promise as dry sorbents for carbon dioxide (CO2 ) capture utilizing their large surface areas. Although there have been considerable efforts to find optimal pore size and geometry for a variety of porous materials, systematic experimental study covering various key parameters beside CO2 uptake, such as isosteric heat and selectivity against other gas, is unavailable. Here, we systemically investigate the pore size effect on the CO2 uptake and selectivity for porous activated carbon. We found that at each temperature and pressure, there exists an optimal intermediate activation condition that makes the pore size most appropriate for CO2 uptake and selectivity. Further activation increases the pore size and weakens CO2 ‐wall interaction. This study provides an important lesson that the pore activation of porous carbon should be controlled at an optimal intermediate point to maximize CO2 ‐wall interaction. Abstract : A perfect fit : There exists a critical pore size in CO2 capture with porous carbon. Excessive pore activation to increase the average pore size and porosity rather decreases CO2 uptake capacity due to weakened CO2 ‐wall interaction. The current investigation provides an important lesson that pore activation should be terminated at an optimal point to maximize CO2 capture performance.